2001
DOI: 10.1063/1.1375144
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous particle image velocimetry and infrared imagery of microscale breaking waves

Abstract: We report the results from a laboratory investigation in which microscale breaking waves were detected using an infrared (IR) imager and two-dimensional (2-D) velocity fields were simultaneously measured using particle image velocimetry (PIV). In addition, the local heat transfer velocity was measured using the controlled flux technique. To the best of our knowledge these are the first measurements of the instantaneous 2-D velocity fields generated beneath microscale breaking waves. Careful measurements of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
74
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(78 citation statements)
references
References 25 publications
4
74
0
Order By: Relevance
“…The rms surface vorticity hjw s ji also gradually increases to 2.0 s À1 in analogy with A B in the renewal term from the phase d. In contrast, in the bore region, the renewed surface fully covers the whole surface after the wavefront temporally recovers the surface at the phase a since significant vorticity, more than twice hjw s ji of the plunging region, disturbs extensively the surface over a long duration. The high temporal correlations between A B and hjw s ji in the both of plunging and bore regions are consistent with the former work by Siddiqui et al [2001].…”
Section: Patterns Of Surface Temperature On Breaking Wavessupporting
confidence: 81%
See 3 more Smart Citations
“…The rms surface vorticity hjw s ji also gradually increases to 2.0 s À1 in analogy with A B in the renewal term from the phase d. In contrast, in the bore region, the renewed surface fully covers the whole surface after the wavefront temporally recovers the surface at the phase a since significant vorticity, more than twice hjw s ji of the plunging region, disturbs extensively the surface over a long duration. The high temporal correlations between A B and hjw s ji in the both of plunging and bore regions are consistent with the former work by Siddiqui et al [2001].…”
Section: Patterns Of Surface Temperature On Breaking Wavessupporting
confidence: 81%
“…[21] On the other hand, a series of studies on sea surface temperatures with infrared imagery by Jessup and his colleagues has revealed that wind-driven microbreaking of ocean waves has a primary role for renewing the surface owing to breaking turbulence, resulting in modulations of the surface temperature [Jessup and Hesany, 1996;Jessup et al, 1997;Wick and Jessup, 1998;Siddiqui et al, 2001;Branch and Jessup, 2007]. The temperature modulation has been observed to appear at different phases in open ocean, which is caused by microbreaking owing to short waves bounded on longer swell waves [Branch and Jessup, 2007].…”
Section: Small-scale Laboratory Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Microbreaking is then marked at the surface by formation of a bulge on the forward face of the wave crest and a train of capillary ripples riding ahead, as observed experimentally by Ebuchi et al [1987], Duncan et al [1999], and Diorio et al [2009]. After the pioneering works by Banner and Phillips [1974] and Okuda [1982], investigations of the water flow exploiting novel imaging techniques have clearly indicated that these surface disturbances are indeed accompanied by the development of a thin surface turbulent sublayer below the wave crest following a downward intrusion of water at the bulge toe [Jessup et al, 1997;Siddiqui et al, 2001;Peirson and Banner, 2003;Zappa et al, 2004].…”
Section: Introductionmentioning
confidence: 92%